PELATIHAN PENINGKATAN KAPASITAS PENGELOLAAN KEUANGAN DESA PADA PERANGKAT DESA BOMERTO - Silvia Hendrayanti; Yoga Nindhita; Achmad Junaidi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2024)
Village financial management is something that really needs to be considered in its implementation. Bomerto Village still requires management of village funds so that they can be utilized as optimally as possible for the progress of the village. The aim of implementing this community service is to provide adequate knowledge and training to village officials in Bomerto village, Wonosobo Regency regarding the management and financial reporting of village funds properly, transparently, accountably, participatively, orderly and disciplined, as well as community service. to the community, this is useful in early prevention of potential misappropriation of village funds so that village fund managers can avoid legal problems in the future. The method for implementing activities uses the Participatory Rural Appraisal (PRA) method with planning stages, namely socialization of activity implementation, counseling on the village fund management system and training in making village financial budgets. From these mentoring activities, good knowledge aspects related to the Definition of Village Fund Management, Government Financial Standards, Village Financial Reporting, Village Financial Accountability, and Transparency have increased significantly in value. Knowledge aspect from 30% to 75%. The increase in scores on the knowledge aspect after village fund management activities shows that these activities are effective in increasing the understanding and ability of village officials in managing village funds.